Knowledge and practice about dietary pattern among diabetic patient. - chaudhary, Sita kumari (2011)
ABSTRACT: This small-scale research study on "Knowledge and Practice about Dietary Pattern among Diabetic Patient", attending out-patient department (OPD) of medicine of Tribhuwan University Teaching Hospital (TUTH). The 50 respondents were selected for this study. The main objective of this study was to assess the Knowledge and Practice of dietary pattern among Diabetic patient who are attending O.P.D of TUTH during the study period. Non probability purposive sampling technique was used for data collection. The data were collected by using semi-structured questionnaires through personal interview. Collected data were analyzed by using descriptive statistics, frequency and percentage and presented in tables. Finding shows majority of the respondents were in the age group 51-60 years. Male and Female were nearly in equal ratio. Eighty percent were educated and around half of respondents had knowledge about diabetic diets. Seventy six percent of respondents had knowledge about exercise. Fifty percent respondents maintained sugar by taking drugs, ninety percent respondents controlled by maintaining blood sugar, and forty percent of respondents controlled normal level of cholesterol. Hundred percent respondents had knowledge to test blood sugar and about eating fruits. Ninety-two respondents had knowledge about avoidance of fasting and eighty- two of respondents had knowledge about hypoglycemia and sign and symptoms of hypoglycemia and hyperglycemia. Majority of respondents had knowledge about consultation of dietician. Ninety-two respondents had knowledge about non curative diabetic disease whereas forty six respondents were service holders. Seventy two percent respondents consumed Sunflower oil, sixty two percent respondents had knowledge about hypoglycemia treatment and immediate taking sugar or glucose water. Ninety two percent respondents had knowledge about affect in eyes and kidneys. Fifty eight respondents had knowledge about once a month regular visit and ninety percent respondents had knowledge about carrying identification card. Almost all respondents had knowledge about avoidance of tobaccos and drinking alcohol.